Pengelolaan Metode Pembelajaran Mandiri bagi Warga Belajar Program Kesetaraan Kejar Paket C di PKBM Bintang Flobamora Kupang - Nirwaning Makleat; Abdul Syukur; Anasius Dei Ndewi (Universitas Pendidikan Mandalika, 2022)
This study aims to describe the planning, implementation and evaluation of the management of independent learning methods for learning residents of the Kejar Paket C equivalence program at PKBM Bintang Flobamora Kupang, East Nusa Tenggara. This study uses a descriptive method with a qualitative approach. Purposive sampling technique was used to determine the research subjects which consisted of 2 tutors and 4 study residents. Data was collected using observation techniques, interviews and documentation studies. Analysis of research data was carried out through data reduction, data presentation and drawing conclusions. In addition, this study also uses triangulation to ensure the validity of the data. The results showed that the learning community was not fully involved in the learning planning stage and the learning objectives were still focused on developing knowledge competencies. The implementation of the independent learning method is also still not fully successful because the learning community still has a wrong understanding of the true meaning of independent learning. The evaluation in the form of a post test that was carried out turned out to be only able to measure the development of cognitive aspects and had not touched other developmental aspects as well as the obstacles faced during the independent learning process in order to improve towards better development.